Clinical Validation and Implications of Dried Blood Spot Sampling of Carbamazepine, Valproic Acid and Phenytoin in Patients with Epilepsy - Kong, Sing Teang; Lim, Shih-Hui; Lee, Wee Beng; Kumar, Pasikanthi Kishore; Wang, Hwee Yi Stella; Ng, Yan Lam Shannon; Wong, Pei Shieen; Ho, Paul C. (PLOS ONE, 2014)
To facilitate therapeutic monitoring of antiepileptic drugs (AEDs) by healthcare professionals for patients with epilepsy (PWE), we applied a GC-MS assay to measure three AEDs: carbamazepine (CBZ), phenytoin (PHT) and valproic acid (VPA) levels concurrently in one dried blood spot (DBS), and validated the DBS-measured levels to their plasma levels. 169 PWE on either mono- or polytherapy of CBZ, PHT or/and VPA were included. One DBS, containing ∼15 µL of blood, was acquired for the simultaneous measurement of the drug levels using GC-MS. Simple Deming regressions were performed to correlate the DBS levels with the plasma levels determined by the conventional immunoturbimetric assay in clinical practice. Statistical analyses of the results were done using MedCalc Version 12.6.1.0 and SPSS 21. DBS concentrations (Cdbs) were well-correlated to the plasma concentrations (Cplasma): r = 0.8381, 0.9305 and 0.8531 for CBZ, PHT and VPA respectively, The conversion formulas from Cdbs to plasma concentrations were [0.89×CdbsCBZ+1.00]µg/mL, [1.11×CdbsPHT−1.00]µg/mL and [0.92×CdbsVPA+12.48]µg/mL respectively. Inclusion of the red blood cells (RBC)/plasma partition ratio (K) and the individual hematocrit levels in the estimation of the theoretical Cplasma from Cdbs of PHT and VPA further improved the identity between the observed and the estimated theoretical Cplasma. Bland-Altman plots indicated that the theoretical and observed Cplasma of PHT and VPA agreed well, and >93.0% of concentrations was within 95% CI (±2SD); and similar agreement (1∶1) was also found between the observed Cdbs and Cplasma of CBZ. As the Cplasma of CBZ, PHT and VPA can be accurately estimated from their Cdbs, DBS can therefore be used for drug monitoring in PWE on any of these AEDs.